POWER QUALITY IMPROVEMENT OF A DSISTRIBUTION SYSTEM BASED ON NEW CUSTOM POWER DEVICES - MOHAMMED OSMAN, BAHR ELDIN SULIMAN (2014)
Due to the market competitions and the enforced regulations, loads based on power electronics converters are on the increase in electrical distribution networks (DNs). Power quality (PQ) problems have been associated with the DNs because of the nonlinear characteristics of power electronics based loads. The integrations of the distributed generations such as, fuel cells, photovoltaic etc., and their accommodations into the new smart DNs has further added to the PQ problems. Moreover, the distribution utilities arc changing towards the smart grids, therefore, PQ for the digital economy in a smart grid distribution system (DS) is now becoming a priority because of varieties in its quality and price option. Therefore, the need to finding new solutions to mitigate PQ problems becomes a necessity. With recent developments in semiconductor switching devices, it is possible to increase the reliability and quality of the distribution supply systems to fulfill the consumer needs by the application of the custom power devices (CPDs).